2014
DOI: 10.18632/oncotarget.2164
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin 1 promotes an aggressive phenotype through epithelial-to-mesenchymal transition in human melanoma

Abstract: Epithelial-to-mesenchymal transition (EMT), in which epithelial cells loose their polarity and become motile mesenchymal cells, is a determinant of melanoma metastasis. We compared gene expression signatures of mesenchymal-like melanoma cells with those of epithelial-like melanoma cells, and identified Thrombospondin 1 (THBS1) as highly up-regulated in the mesenchymal phenotype. This study investigated whether THBS1, a major physiological activator of transforming growth factor (TGF)-beta, is involved in melan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(125 citation statements)
references
References 65 publications
6
119
0
Order By: Relevance
“…Metastatic volume inside lungs is indicated at the right bottom of the picture over the last 2 years pointing out the contribution of TSP-1 in melanoma metastatic program. TSP-1 was indeed first described in 2014 as promoting an epithelial-to-mesenchymal transition (EMT) in human melanoma cells [10]. At the same time, Borsotti et al identified TSP-1 as a main actor of a motility and metastatic program in melanoma [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metastatic volume inside lungs is indicated at the right bottom of the picture over the last 2 years pointing out the contribution of TSP-1 in melanoma metastatic program. TSP-1 was indeed first described in 2014 as promoting an epithelial-to-mesenchymal transition (EMT) in human melanoma cells [10]. At the same time, Borsotti et al identified TSP-1 as a main actor of a motility and metastatic program in melanoma [13].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two research teams independently reported THBS1 gene expression to be elevated in chemoresistant and motile melanoma cells [10,13], thus supporting the concept of a TSP-1-driven invasion program in melanoma. By overlapping gene expression data with PPI information registered in the human protein reference database (HPRD) [21], we here demonstrate that a THBS1-centered whole network of genes encoding for ECM proteins and receptors cross-interacting with each other is actually overexpressed in melanoma (Fig.…”
Section: Thbs1 Interaction Network Is Overexpressed In Malignant Melamentioning
confidence: 91%
See 1 more Smart Citation
“…Epithelial-to-mesenchymal transition (EMT) is a cellular process during which epithelial cells undergo a phenotypic switch to become more aggressive and motile mesenchymal cells [62] . The process of EMT is also a major contributor for metastasis and drug resistance [61] .…”
Section: Epithelial-to-mesenchymal Transitionmentioning
confidence: 99%
“…33 In addition, we found genes that have been shown to be important in the epithelial-mesenchymal transition (PVRL1, THBS1, MMP-13). [34][35][36] Given the background of these genes, we proposed that the SSEA-1C cell population may have a slightly different identity expressing higher levels of genes found in mesenchymal stem cells and mesoderm/mesendoderm.…”
Section: Enhanced Reprogramming Could Be Determined In Single Danish mentioning
confidence: 99%